Appreciative inquiry change at the speed of imagination - Watkins, Jane Magruder; Mohr, Bernard J.; Kelly, Ralph, 1938-; ProQuest (Firm) (San Francisco : Pfeiffer, 2011)
"This book shows how the Appreciative Inquiry process helps OD and HR professionals tap into inspiring "high point" accounts of personal or collective capacity. This new edition puts the focus on how AI really works and adds guidelines on how to apply AI in a variety of organizational situations and for a variety of initiatives such as coaching, leadership development, strategic planning, and teambuilding. It contains tools and other resources to help with immediate use in the workplace and new and updated case studies that show how it really works."--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Organizational change; Appreciative inquiry; Electronic books